2004
DOI: 10.1002/hed.20073
|View full text |Cite
|
Sign up to set email alerts
|

LigaSure versus clamp‐and‐tie thyroidectomy for benign nodular disease

Abstract: The use of the LigaSure vessel sealer for thyroid surgery is an effective and safe alternative that reduces the overall operative time and could be successfully applied through a narrow surgical incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
73
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 26 publications
10
73
4
2
Order By: Relevance
“…Petrakis et al [6] in their study found intraoperative total blood loss was similar between the two groups, but postoperative drain volume was less in Ligasure group than in other (21±15 mL; p IJBR (2015) 6 (06) www.ssjournals.com <.01).In our study postoperative complications were observed in 11(10.18%) cases. Barbaros et al [7] in 2006 used Ligasure in patients with hyperthyroidism and found the complication rates of the Ligasure and conventional thyroidectomy groups were 4 and 6%, respectively (p>0.05).…”
Section: Discussionsupporting
confidence: 47%
“…Petrakis et al [6] in their study found intraoperative total blood loss was similar between the two groups, but postoperative drain volume was less in Ligasure group than in other (21±15 mL; p IJBR (2015) 6 (06) www.ssjournals.com <.01).In our study postoperative complications were observed in 11(10.18%) cases. Barbaros et al [7] in 2006 used Ligasure in patients with hyperthyroidism and found the complication rates of the Ligasure and conventional thyroidectomy groups were 4 and 6%, respectively (p>0.05).…”
Section: Discussionsupporting
confidence: 47%
“…The primary application for the HS in the otolaryngological literature is its use for tonsillectomy and thyroidectomy. The use of the HS has also been described in excising cancer of the tongue and soft palate [7], submandibular sialoadenectomy [8], parotidectomy, treating allergic rhinitis by means of inferior turbinate alteration, and surgical treatment of rhinophyma [9]. Unlike the variable results described with the use of the HS in tonsillectomy, literature is consistent concerning the usefulness of the harmonic scalpel in thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported results of using LigaSure in thyroid surgery have been fairly discordant. Several authors reported a reduction in complications such as transient recurrent palsy and transient hypoparathyroidism and shorter operating times, 12 whereas others reported a shorter operating time but no change in the incidence of complications. [13][14][15] Some authors even reported no difference in operating times or the incidence of complications between LigaSure and traditional hemostatic methods.…”
mentioning
confidence: 99%